THE IMPACT OF TRANSACTION COSTS ON MANAGEMENT DECISIONS (ON THE EXAMPLE OF UKRAINIAN COMPANIES) - Shevchuk, Olena; Mazhara, Glib; Semenchenko, Nataliia (Baltic Journal of Economic Studies, 2022)
The purpose of the article is to study the impact of transaction costs on managerial decision-making on the example of Ukrainian enterprises. The article notes that, despite the significant achievements of the institutional theory, there are still questions about the clarity of understanding of its key concepts and definitions, the content of transaction costs and the concept of their minimization, the expediency and efficiency of the existence of certain types of transaction costs. The subject of the study is the essence of transaction costs of the enterprise and their modern classification. The methodological basis of the study was an integrated approach to the essence and classification of transaction costs, as well as general scientific and special research methods: retrospective and systematic analysis, comparison and generalization, grouping and sampling, methods of building linear and nonlinear economic and statistical models with constraints. As noted above, the main issue of the study was the classification of transaction costs. The economic situation in Ukraine was assessed, which allowed to determine that transaction costs are quite high for enterprises due to: insufficient development of markets, unformed structure of institutions, complex and ambiguous legislation, significant tax pressure and existing facts of corruption. The authors noted that the list of components of transaction costs is constantly updated due to the complication of the socio-economic conditions for doing business associated with crisis-forming force majeure factors (in particular, the COVID-19 pandemic), which have become very significant for the world economy and have significantly changed approaches to the allocation of investment resources. As a result of the study, it is proposed to supplement the existing classification of transaction costs with costs associated with adapting to new business conditions ("adaptation cost"), which together characterize the ability of an enterprise to adapt to new conditions of functioning and development. The main conclusions of the study include the fact that, given current trends, reducing transaction costs is becoming a priority issue. At the same time, in the context of the proposed classification, a model for minimizing transaction costs was developed for the first time, which includes a modern classification of transaction costs and provides the possibility of their modeling for a more complete and logical calculation. According to the authors, the presented model will provide an opportunity to more correctly determine the effectiveness of management decisions related to investments in the core business of the enterprise. It is important to note that, given the basic provisions of institutional theory, a significant amount of transaction costs, in principle, can neutralize the investment process. Thus, the study is of both theoretical and practical importance and gives an idea of solving a number of both industrial and social problems and can become the basis for further research.